Trichtlinnburg I, II, III : An urban affair = Een affaire met de stad = Ein städtisches Abenteuer = Linnajuhtum. - Amanshauser, Hildegund; Brams, Koen; Dölle, Mariëtte; Eggermont, Mique; Hauffen, Michael; Kurg, Andres; Lesage, Dieter; Matthys, Kobe; Muizelaar, Carole; Pedanik, Mare; Sachs, Hinrich; Siib, Liina; et al. (Tallinn Salzburg Maastricht : Center for Contemporary Arts Salzburger Kunstverein Jan Van Eyck Akademie, 2005)
Alender, Joko ; Bauer, Ralph ; Bernstein, Ron ; bolwerK Interrational ; Bozis, Eriks ; Dector, Michel ; Deutschbauer, Julius ; Dupuy, Michel ; Erenurm, Bie ; Essenson, Katrin ; Gansterer, Nikolaus ; Garrison, Geoffrey ; gold extra et al. ; Ivekovic, Sanja ; Kurismaa, Kaarel ; Kuss, Kai ; Kwan, Will ; Lanzinger, Pia ; Lapitkova, Zuzana ; Lemke, Christine ; LIGNA ; Mitterhuber, Manuela ; Mörschbacher, Thomas ; Norman, Nils ; Ojaver, Jüri ; Paaver, Toomas ; Pennanen, Anu ; Plink, Villu ; Rool, Andy ; Saarepuu, Silja ; Spring, Gerhard ; stadtraum.org ; Tammetalu, Tiina ; Tiigisoon, Karri ; Transparadiso ; Valk, Veronika ; Vallner, Siiri ; Video Sisters
Trichtlinnburg project, public space, Tallin, Salzburg, Maastricht, from 5 May to 5 June 2005
boek